Ilmu farmasi ditinjau dari segi ontologi, epistemologi, dan aksiologi - Khanifah, Nuha Nafi’atul (Maliki Interdisciplinary Journal, 2025)
This article explores pharmaceutical science from the perspective of the philosophy of science, which includes three main dimensions, namely ontology, epistemology, and axiology. Ontologically, pharmacy focuses on the nature and existence of pharmacy as an object of study, both drugs derived from natural and synthetic materials, and its close relationship with other disciplines such as biology, chemistry, and physics. From the epistemological side, pharmacy studies the process of acquiring scientific knowledge through observation, experimentation, and verification, which supports the development of theories and applications in the health sector. Meanwhile, axiology highlights the benefits of pharmaceutical science in life, including its role in healing, disease prevention, and body care. A deep understanding of these three aspects allows pharmaceutical science to continue to develop innovatively, responsibly, and make significant contributions to society.